Sociocultural experiences of first year students: A case study of a selected university in South Africa - Kanyopa, Theresia Joakim; Mokhele-Makgalwa, Matseliso; Mufanechiya, Albert (Edelweiss Applied Science and Technology, 2024)
The transition into higher education institutions is a perilous life stage for every first-year university student around the world. The aim of the study is to explore the sociocultural and lived experiences of first year students in one of the universities in South Africa. This study adopted qualitative approach which involved the use of focus group discussion and questionnaire for data triangulation. The diffusion of innovation theory of learning was used to frame the study. Convenient and purposive sampling were employed to select the sample population of 93 students who are coming from different provinces of South Africa, and registered for the first time at selected university to pursue their Bachelor Degrees in the faculty of Education. Findings revealed positive and negative experiences, and the study suggests the construction of knowledge through active engagement and involvement of these students as to help them to embrace both learning opportunities and challenges while studying at the university.